Visual-Cerebellar Pathways and Their Roles in the Control of Avian Flight - Wylie, Douglas R.; Gutiérrez-Ibáñez, Cristián; Gaede, Andrea H.; Altshuler, Douglas L.; Iwaniuk, Andrew N. (Frontiers in Neuroscience, 2018)
In this paper, we review the connections and physiology of visual pathways to the cerebellum in birds and consider their role in flight. We emphasize that there are two visual pathways to the cerebellum. One is to the vestibulocerebellum (folia IXcd and X) that originates from two retinal-recipient nuclei that process optic flow: the nucleus of the basal optic root (nBOR) and the pretectal nucleus lentiformis mesencephali (LM). The second is to the oculomotor cerebellum (folia VI-VIII), which receives optic flow information, mainly from LM, but also local visual motion information from the optic tectum, and other visual information from the ventral lateral geniculate nucleus (Glv). The tectum, LM and Glv are all intimately connected with the pontine nuclei, which also project to the oculomotor cerebellum. We believe this rich integration of visual information in the cerebellum is important for analyzing motion parallax that occurs during flight. Finally, we extend upon a suggestion by Ibbotson (2017) that the hypertrophy that is observed in LM in hummingbirds might be due to an increase in the processing demands associated with the pathway to the oculomotor cerebellum as they fly through a cluttered environment while feeding.